(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Walker Percy, one of the major South American novelists dealing with the predicament of contemporary man, focuses on existentialistic streaks in his fictional world. Like others, he has adopted this fictional method for the analysis and development of character and also as a new structure for the achievement of narrative progression. He knew himself, maintains Alfred Kazin, as “part of History, a larger meaning, whether it was America the colossus, the juggernaut, the great melting pot into which he did not want to melt… There was an unconscious depth to his writing.”1 As in existential fiction, opines Richard Lehan, Percy’s novels take place in “a prolapsed world, often cut off from the ordinary workaday world, where characters are haunted by the past and bound by the absurdity of their situation.”2 Percy adds to this two states of narrative consciousness, one of perception and the other of reflection, and also a sense of the grotesque.